PENYULUHAN PEKEBUNAN JERUK DAN CABAI UNTUK KESEJAHTERAAN MASYARAKAT DESA MARGALUYU, PENGALENGAN, BANDUNG - Sovitriana, Rilla; Budilaksono, Sularso; Dewi, Euis Puspita; Nasution, Evi Syafrida; Trikariastoto, ST; Nurina, Nurina; Kencana, Woro Harkandi; Effendi, Maya Syafriana; Farida, Farida; Thantawi, Ahmad Muhammad (Universitas Mataram, 2024)
In Margaluyu Village, Pengalengan, Bandung, West Java, there are a number of plantation lands which have a vital role in the local and national economy. Pangalengan is an agricultural, livestock and animal husbandry area. Many tea and quinine plantations are managed by PTPN. Margaluyu Village has great agricultural potential, especially for cultivating oranges and chilies. However, it is necessary to increase farmers' productivity and income through counseling on appropriate cultivation techniques. Increase farmers' knowledge and skills as well as their productivity and income through extension activities on orange and chili plantations. Through counseling and assistance, community service aims to encourage the adoption of sustainable agricultural practices, such as the use of organic fertilizer, integrated control of pests and plant diseases, and good soil management. Extension is carried out through training, group discussions, field training, mentoring, and periodic evaluations using questionnaires and interviews. The activity method carried out is in the form of training and discussions between farmers and the community with resource persons by conducting direct outreach. Extension to farmers in Margaluyu Village through lecture sessions, presentations and discussions about effective and sustainable agricultural practices. Achieved an increase in farmer knowledge, harvest productivity, quality of results, and an increase in farmer income. Increasing farmers' knowledge and skills so that farmers become more skilled in utilizing existing resources to maximize harvest yields and minimize the risk of loss. These activities have a significant positive impact on farmers and overall village prosperity. Adoption of sustainable agricultural practices, increasing farmers' knowledge and skills, as well as increasing farmers' productivity and welfare are things that can be achieved through this activity.